Financial viability of developing a sago plantation in the Philippines - Acuña, Thaddeus R.; Laorden, Nikko L.; Fedillaga, Albert Joseph A.; Ramoneda, Brenda M.; Concepcion, Sylvia B. (2016)
Establishing a sago plantation is an essential element in promoting and developing a sago industry in the Philippines. The long gestation period of sago palms, together with huge investment requirements for commercial propagation and other challenges, would naturally leads us to ask if it is viable to establish a sago plantation in the Philippines. To guide the development of sago industry in the Philippines, we propose a development framework with three phases: (1) establishing a sago plantation anchored on the National Greening Program, (2) commercializing sago starch extraction by setting up community-based enterprise, and (3) manufacturing of high-value starch derivatives. By evaluating key assumptions and financial criteria such as the net present value, internal rate of return, and payback period of the first two phases, we show that the establishment of sago plantation and community-based sago enterprises are financially viable. Further studies that will assess the economic, social, and environment factors affecting the development of the sago industry in the country is recommended.
Keywords: Sago industry; Sago palms -- Economic aspects